Generalized Schur functions and passive discrete-time realizations - Lilleberg, Lassi (Vaasan yliopisto, 2021)
Passive discrete-time systems or contractive operator colligations in Pontryagin space setting are investigated. Transfer functions of such systems are generalized Schur functions, and hence these systems offer state space realizations for such functions. The approach here is to generalize the theory of minimal passive systems, pioneered by D.Z. Arov, from Hilbert space setting to indefinite setting, and then combine it with the theory of generalized Schur functions, reproducing kernels and co-isometric colligations; these are the subjects, which were pioneered by M. G. Krein and H. Langer and L. de Branges. The concept of the defect function is expanded for generalized Schur functions by using optimal minimal realizations. Defect functions are used to analyze how behaviour of radial limit values on the unit circle affects the properties of certain realizations of generalized Schur functions. It is shown that generalized Schur functions with zero defect functions have stronger realizations than generic Schur functions. These results generalize the results obtained earlier in the Hilbert space setting for rational unitary functions and bi-inner functions. Furthermore, weak and unitary similarity mappings between the state spaces of specific realizations of generalized Schur functions are investigated. A criterion involving a scattering suboperator obtained by D.Z. Arov and M.A. Nudelman, when all minimal passive realizations of the same Schur function are unitarily similar, is extended to the class of generalized Schur functions. For symmetric generalized Schur functions, it is shown that negative index of the weak similarity mapping between an optimal minimal realization and its dual can be used to decide when such a function is a generalized Nevanlinna function.

Väitöskirjassa tarkastellaan passiivisia diskreettiaikaisia systeemejä Pontryaginin avaruuksissa. Kyseessä olevat systeemit voidaan samaistaa kontraktiivisten operaattorikolligaatioden kanssa. Niiden siirtofunktiot ovat yleistettyjä Schur-funktioita. D.Z. Arovin tulokset minimaalisista passiivisista systeemeistä Hilbertin avaruuksissa yleistetään indefiniitteihin avaruuksiin. Saatuja tuloksia sovelletaan M.G. Kreinin ja H. Langerin sekä L. de Brangesin teoriaan yleistetyistä Schur-funktioista, ydinavaruuksista ja koisometrisista kolligaatioista. Defektifunktiot määritellään yleistetyille Schur-funktioille käyttämällä optimaalisia ja minimaalisia realisaatioita. Defektifunktioiden ominaisuuksien ja yleistettyjen Schur-funktioiden realisaatioiden ominaisuuksien yhteyttä analysoidaan. Niiden yleistettyjen Schur-funktioiden, joiden defektifunktiot häviävät, realisaatiolla on vahvoja ominaisuuksia. Johdetut tulokset ovat yleistyksiä aiemmin tunnetuille unitaarisia rationaalifunktioita ja tavallisia sisäfunktioita koskeville tuloksille. Tutkimusteemana ovat myös heikot ja unitaariset similariteetit yleistettyjen Schur-funktioiden realisaatioiden välillä. D.Z. Arovin ja M.A. Nudelmanin todistama kriteeri siitä, milloin kaikki minimaaliset ja passiiviset realisaatiot ovat unitaarisesti similaarisia, laajennetaan käsittämään myös yleistettyjen Schur-funktioiden luokka. Tutkimalla symmetrisen yleistetyn Schur-funktion optimaalisen ja minimaalisen realisaation sekä tämän duaalin välisen heikon similariteetin negatiivista indeksiä, saadaan kriteeri sille, milloin yleistetty symmetrinen Schur-funktio on myös yleistetty Nevanlinna-funktio.
Yleistetyt Schur-funktiot ja passiiviset systeemit
Keywords: operator colligation; passive system; contractive operator; transfer function; generalized Schur class; generalized Nevanlinna class; inner function; Hilbert space; mathematics; functional analysis; fi=Matematiikka|en=Mathematics|